PENGARUH MOTIVASI KERJA, KOMUNIKASI ANTAR PRIBADI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEJABAT STRUKTURAL DAN DOSEN TETAP DI BEBERAPA PERGURUAN TINGGI SWASTA DI JAKARTA - Ismuhadjar, Ismuhadjar (JURNAL BISNIS STRATEGI, 2006)
The objective of this study is to search empirically the influences ofjob motivation, interpersonal communication, and organizational commitment towardjob-performance. Sample of the study consists of 90 respondents randomly selected from structural and academic staffs from 4 (four) private higher education institutions within The Coordination of Private Higher Educational Institutions, Region Ill (Koordinasi Perguruan Tinggi Swasta Wilayah Ill) Jakarta. Hypotheses of the study stated that :Â  " There are positive and significant influences of motivation, interpersonal communication, and organizational commitment, individually and simultaneuosly towardjob-performance". The result of the study definitely supports the said hypotheses. Based on the result of the study it is suggested to management of private higher educational institutions in order to upgrade the Job-performance of structural and academic staffs continously by upgrading the Job-motivation, Interpersonal communication, and their commitment to the institution. To the other researchers it is recommended to do the subsequent research using other variables, including Job-ability, Job-satisfaction and Job-facilities and their influence onto job-performance.